Ontology engineering in a networked world - Suarez-Figueroa, Mari Carmen (Springer, 2012)
This book presents the NeOn Methodology Framework, which includes nine scenarios for collaboratively building ontologies and ontology networks. It provides the reader with a description of the key activities relevant to the ontology engineering life-cycle.